2017
DOI: 10.1186/s40529-017-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal regulation of the floral scent emission by light and circadian rhythm in the Phalaenopsis orchids

Abstract: Background Phalaenopsis bellina and its closely related species, P. violacea, emit linalool, geraniol and their derivatives as the predominant monoterpenes at the full-bloom stages. Geranyl diphosphate synthase (PbGDPS) is the key enzyme that converts precursors for monoterpene biosynthesis. Besides the monoterpenes being synthesized in concert with floral development stages, we noticed that the scent emission of P. bellina and P. violacea was detected mainly in the daytime.ResultsThe monoterpenes of P. violac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…PbGDPS shows flower-specific expression, and its highest expression is concurrent with maximal emissions of monoterpenoids on day 5 post-anthesis (D+5), which suggests a crucial role of PbGDPS in floral scent production in P. bellina ( Hsiao et al , 2008 ). Recently, we found that the emission of monoterpenes is under the control of light and a circadian rhythm in Phalaenopsis orchids ( Chuang et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…PbGDPS shows flower-specific expression, and its highest expression is concurrent with maximal emissions of monoterpenoids on day 5 post-anthesis (D+5), which suggests a crucial role of PbGDPS in floral scent production in P. bellina ( Hsiao et al , 2008 ). Recently, we found that the emission of monoterpenes is under the control of light and a circadian rhythm in Phalaenopsis orchids ( Chuang et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In constant light (500 μmol·m −2 s −1 ), P. violacea emitted mostly monoterpenes whose levels decreased in constant darkness. PbNAC1, which regulates the synthesis of monoterpenes, interacts with long hypocotyl 5 (HY5), which is a positive transcription factor involved in the responsiveness of plants to light [ 5 , 39 ]. DoGES1 demonstrated fluctuations throughout the day, increasing at 8:00, then decreasing from 11:00 to 17:00, peaking at 11:00 ( Figure 7 ), corresponding to the increase and then decrease in geraniol content at the same harvest time points, with the highest value observed at 14:00, suggesting that the emission of monoterpenes may have a diurnal rhythm in D. officinale petals.…”
Section: Discussionmentioning
confidence: 99%
“…These individual plants were collected from various orchid nurseries across Taiwan (details in Supplementary Table 1 ). Both P. I-Hsin Venus and P. Meidarland Bellina Age are commercial scented cultivars with monoterpenes as their major scent compounds ( Chuang et al, 2017 ), whose ancestries contain multiple scent species as the following: P. I-Hsin Venus - P. amboinensis (25%), P. equestris (25%), P. venosa (18.75%), P. violacea (15.63%), P. lueddemanniana (3.13%); P. Meidarland Bellina Age - P. bellina (50%), P. violacea (24.22%), P. venosa (15.63%), P. amboinensis (3.91%), P. lueddemanniana (3.13%) via ORCHIDEYA.CA 1 . All the plant materials were grown in the greenhouse at National Cheng Kung University (NCKU) under natural light and surrounding temperature from 27 to 30°C in spring and summer with 75–85% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the floral VOCs of 12 Phalaenopsis orchids was carried out according to the previous studies ( Hsiao et al, 2006 ; Chuang et al, 2017 ). The VOCs were collected during the most emitted scent period (from 10:00 to 16:00) by using solid phase extraction system (DSC-Si and DCS-18, Supelco, United States) as described ( Chuang et al, 2017 ), and the compounds were then identified by using gas chromatography/high-resolution mass spectrometry (GC/HRMS) at the NCKU Instrument Center ( Hsiao et al, 2006 ). To assess the amounts of each compound, 1 μg of ethyl myristate was recruited as the internal standard (Fluka, Honeywell, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation